Skyward Flight : the collection - Sanderson, Brandon; Patterson, Janci (Sanderson, Brandon. Skyward (Series), 2022)
"Return to the planet Detritus with FM, Alanik, and Jorgen in this must-have three-novella collection featuring exclusive character art and deleted scenes from Skyward with commentary from Brandon Sanderson"--